Can a location-based game make players mindful during the gameplay? A case study of Pokémon GO. (9th February 2023) - Pyae, Aung
Recently, 'mindfulness' has been of interest to researchers in psychology as an intervention to promote psychological well-being. Due to recent technological advances, mindfulness-based interventions can now be delivered through digital platforms including mobile phones. Whilst the literature shows the promise of mindfulness-based applications for users, there is limited research into location-based games (LBGs) for mindfulness. To address this gap, in this study, a questionnaire was administered to Pokémon GO game players to gauge mindfulness and better understand which aspects of their play contributed to their mindfulness. The findings suggest that the Pokémon GO game is promising to promote players' mindfulness through gameplay. Further, the findings shed light on the level of mindfulness as measured by player's attention, focus, awareness, and acceptance in the gameplay. Lastly, the application of LBGs deserves a wider interest and attention from researchers due to their demonstrated potential to promote people's psychological well-being by improving mindfulness.